2013
DOI: 10.1103/physrevd.88.063513
|View full text |Cite
|
Sign up to set email alerts
|

Imprint of primordial non-Gaussianity on dark matter halo profiles

Abstract: We study the impact of primordial non-Gaussianity on the density profile of dark matter halos by using the semianalytical model introduced recently by Dalal et al. which relates the peaks of the initial linear density field to the final density profile of dark matter halos. Models with primordial non-Gaussianity typically produce an initial density field that differs from that produced in Gaussian models. We use the path-integral formulation of excursion set theory to calculate the non-Gaussian corrections to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
(40 reference statements)
1
8
0
Order By: Relevance
“…These results are in line with the predictions that f NL changes the internal structure of cluster profiles, as a result of an increase/decrease of cluster concentrations for positive/negative f NL (Smith, Desjacques & Marian 2011;Moradinezhad Dizgah, Dodelson & Riotto 2013). The impact on cluster scaling relations is mostly due to changes in the evolution of their normalizations.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are in line with the predictions that f NL changes the internal structure of cluster profiles, as a result of an increase/decrease of cluster concentrations for positive/negative f NL (Smith, Desjacques & Marian 2011;Moradinezhad Dizgah, Dodelson & Riotto 2013). The impact on cluster scaling relations is mostly due to changes in the evolution of their normalizations.…”
Section: Discussionsupporting
confidence: 90%
“…More sophisticated approaches rely on galaxy cluster scaling relations derived from hydrodynamic or N-body simulations, calibrated by observations, that do not include primordial non-gaussianities (see eg Mak & Pierpaoli 2012;Roncarelli et al 2010). This procedure is clearly not ideal given that non-gaussianities are known to influence the internal structure of clusters (Smith, Desjacques & Marian 2011;Moradinezhad Dizgah, Dodelson & Riotto 2013) and therefore they may cause significant changes in the slope and normalization of galaxy cluster scalings. The study of the impact of PNG on cluster scaling relations is also essential for an accurate characterization of the physical state of the ICM gass and to assess the relative strength of cosmological effects shaping the evolution of galaxy clusters.…”
Section: Introductionmentioning
confidence: 99%
“…In all those studies it has been found that the presence of pNG modifies the abundances of halos and voids increasingly with the rarity of the object. While in principle the presence of pNG might also alter the density profiles of rare objects, the impact on halo profiles has been observed to be small (Moradinezhad Dizgah et al 2013) and a similar study for voids that is underway shows no perceptible differences on void profiles. 1 Furthermore, following an observation from Dalal et al (2008); Desjacques et al (2009), pNG leads to strongly scaledependent bias that impacts the large-scale clustering of rare objects (peaks of the density distribution such as halos) which hence can be used to constrain pNG from large scale structure (Slosar et al 2008).…”
Section: Abundance and Large Scale Clustering Of Rare Objectsmentioning
confidence: 90%
“…The primordial non-Gaussianity can be imprinted even in the profiles of the galactic halos (Moradinezhad Dizgah, Dodelson & Riotto 2013), thus linking the latter to the inflationary phase of the Universe . Halo properties can thus be probes for the nature of perturbations; for example, even though we presently possess no observable evidence of non-adiabatic (iso-curvature) perturbations, we have strong constraints on their possible resistance and it was shown that during re-ionization the iso-curvature modes are transferred to adiabatic ones (Weinberg 2004).…”
Section: Introductionmentioning
confidence: 99%